2013
DOI: 10.4269/ajtmh.13-0089
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluation of a New Rapid Test for Detecting Wuchereria bancrofti Antigen in Human Blood

Abstract: Global Program to Eliminate Lymphatic Filariasis (GPELF) guidelines call for using filarial antigen testing to identify endemic areas that require mass drug administration (MDA) and for post-MDA surveillance. We compared a new filarial antigen test (the Alere Filariasis Test Strip) with the reference BinaxNOW Filariasis card test that has been used by the GPELF for more than 10 years. Laboratory testing of 227 archived serum or plasma samples showed that the two tests had similar high rates of sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
112
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 11 publications
6
112
1
Order By: Relevance
“…A recently published study used a similar scoring system to evaluate the Alere Filariasis Test Strip that is expected to replace the ICT test in the near future. 25 Although the Test Strip was more sensitive than the ICT test in that study, antigen scores for blood samples that were positive by either test were highly correlated. Note that there is no additional cost associated with scoring filarial antigen tests, and scores can be written directly on the cards.…”
mentioning
confidence: 65%
“…A recently published study used a similar scoring system to evaluate the Alere Filariasis Test Strip that is expected to replace the ICT test in the near future. 25 Although the Test Strip was more sensitive than the ICT test in that study, antigen scores for blood samples that were positive by either test were highly correlated. Note that there is no additional cost associated with scoring filarial antigen tests, and scores can be written directly on the cards.…”
mentioning
confidence: 65%
“…The immunochromatography card test (ICT), which detects an adult female antigen, is the tool of choice for determining the areas in which levels of W. bancrofti infection have been reduced to a point where transmission is no longer sustainable and therefore MDA programs can cease [23]. A new rapid antigen test (Alere Filariasis Test Strip) with increased sensitivity and greater stability has become available [24]. Although the filariasis card test has been used for more than 10 years, recent studies have shown false-positive results in patients with high L. loa microfilaremia [25].…”
Section: Reviewmentioning
confidence: 99%
“…In 1997, a rapid, card-based diagnostic test (BinaxNOW® Filariasis) was developed to detect circulating adult worm antigen (235). Recently, a new antigen test (Alere Filariasis Test Strip) was developed to increase sensitivity of diagnosis (234).…”
Section: Diseasementioning
confidence: 99%